Antibacterial activity of constituents from Salvia buchananii Hedge (Lamiaceae). (December 2015) - Bisio, Angela; Schito, Anna Maria; Parricchi, Anita; Mele, Giacomo; Romussi, Giovanni; Malafronte, Nicola; Oliva, Patrizia; Tommasi, Nunziatina De
Graphical abstract: Highlights: Three new and eight known clerodane diterpenes were isolated from Salvia buchananii . S. aureus, S. epidermidis, S. agalactiae, E. faecium, E. faecalis clinical strains. The extract exhibited good activity against Gram-positive species. UA/OA mixture showed good antimicrobial activity against several Gram-positive species. Diterpenes 3, 6, 8 and 9 showed moderate inhibitory activity on Enterococcus species. Abstract: The dichloromethane extract obtained from the aerial parts of Salvia buchananii Hedge was investigated for its antimicrobial properties following a bioassay-oriented fractionation approach. The extract displayed a clear inhibitory activity against several Gram-positive multidrug-resistant clinical strains including Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus agalactiae, Enterococcus faecium and Enterococcus faecalis. No activity was observed on Gram-negative strains and on Candida species. Phytochemical investigation of this extract led to the isolation of three new clerodane diterpenes (5, 6 and8 ) and eight known clerodane diterpenes (1-4, 7, 9-11 ) as well as ursolic (UA ) and oleanolic (OA ) acids. Their structures were established by extensive 1D, 2D NMR and HR-MS spectroscopic methods. The mixtureUA /OA manifested a broad and powerful activity on several Gram-positive species, while diterpenes3, 6, 8 and9 showed moderate inhibitory activity on the Enterococcus species.